ANALISIS DAMPAK STRATEGI OFFSHORE OUTSOURCING DALAM BISNIS FAST FASHION TERHADAP DEGRADASI LINGKUNGAN DI BANGLADESH - Trisha Caicartica Lovinta Nugraha, (2023)
Due to it's massive influence to the consumers around the world, fast fashion is probably a very familiar term that most of us have heard. Other than it's influence, fast fashion is also well known as a business model that posess a very complicated supply chain. Because of that nature, they are often caught up in non ethical practices towards it's workers as well as the environment. Unfortunately, as one of the biggest producing fast fashion countries in the world, Bangladesh doesn't seem to mind about the destructive nature of fast fashion and turn a blind eye towards its effect. Therefore, this research was aimed to provide an explanation of how offshore outsourcing dynamics in fast fashion supply chain causing decline to Bangladesh's environmental quality through ready made garment sector and how the government involved in the case under neoliberal influence using qualitative methods and study case approach. As a result, researcher found that offshore outsourcing strategy in fast fashion business caused a numerous effect on environment such as water contamination, air pollution, and waste buildup on the ground.